2021
DOI: 10.1371/journal.pone.0252035
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating randomized clinical trials of psychological interventions: Impact of response shift on the interpretation of trial results

Abstract: Background Effectiveness of psychological treatment is often assessed using patient-reported health evaluations. However, comparison of such scores over time can be hampered due to a change in the meaning of self-evaluations, called ‘response shift’. Insight into the occurrence of response shift seems especially relevant in the context of psychological interventions, as they often purposefully intend to change patients’ frames of reference. Aims The overall aim is to gain insight into the general relevance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Put differently, while CBT induced a discrepancy between the observed scores and target construct, this did not affect the measured reduction in fatigue severity after CBT. This is in line with recent studies that found a limited impact of response shift on change in the target construct [22,54]. While the detected response shifts in this study were of a large magnitude, they occurred only on a single item per trial, thereby limiting their impact on overall fatigue severity, as measured by eight items.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Put differently, while CBT induced a discrepancy between the observed scores and target construct, this did not affect the measured reduction in fatigue severity after CBT. This is in line with recent studies that found a limited impact of response shift on change in the target construct [22,54]. While the detected response shifts in this study were of a large magnitude, they occurred only on a single item per trial, thereby limiting their impact on overall fatigue severity, as measured by eight items.…”
Section: Discussionsupporting
confidence: 91%
“…In the Cancer-and Diabetes-trials, changes in some fatigue-related cognitions and perceptions showed small associations with the detected response shift on the item "I tire easily." Measures of changes in cognitions and perceptions might not be perfect operationalizations of changes in meaning and the method applied to investigate their relation is not well established yet (however, see also [22,54]). Nevertheless, these results may suggest that cognitions and perceptions could be part of the mechanisms underlying the detected response shift.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 17 articles were predominantly secondary or post-hoc analyses (n = 12) [ 34 45 ], rather than explicitly designing the study to address response-shift effects (n = 5) [ 19 , 46 49 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%